Performance and emissions of diesel engine combustion lubricated with Jatropha bio-lubricant and MWCNT additive - Rajendra Uppar; P. Dinesha; Shiva Kumar (Scientific Reports)
Abstract Vegetable oil-based lubricants, modified through transesterification and epoxidation, present a sustainable alternative to mineral lubricants for transport and industrial use. This study evaluates epoxidized jatropha oil (EJA) enhanced with multi-walled carbon nanotubes (MWCNT) as a bio-lubricant for compression ignition engines. MWCNT, dispersed in EJA using an ultrasonic probe sonicator with Triton X-100 as a surfactant, was tested at nanoparticle concentrations from 0.5 to 2 wt%. Engine performance and emission characteristics were assessed using SAE 20W40, EJA, and EJA-MWCNT in a four-stroke diesel engine. Results showed that EJA with 2 wt% MWCNT reduced friction power by 39.13% compared to SAE 20W40 and decreased brake specific energy consumption by 6.11%, while lowering emissions of hydrocarbons, carbon monoxide, and smoke. These findings highlight EJA-MWCNT as a promising lubricant for diesel engines, enhancing efficiency and reducing pollutants, making it a viable eco-friendly substitute for diminishing petroleum resources.